2019
DOI: 10.3389/fnut.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Multiple Impacts of Household Food Waste

Abstract: The Commission for Environmental Cooperation (CEC) has estimated that Canadian households waste 85 kg of food per person annually. Food waste has become an increasingly common focus for policy, regulation, interventions, and awareness-raising efforts in Canada. However, there is still a relative dearth of data to inform such decision-making processes or to provide narratives to contextualize behavior change efforts. In this paper, we describe the results of an uncommonly detailed observational study of househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 31 publications
2
57
0
9
Order By: Relevance
“…The wasting of food produced for human consumption has been connected to issues such as climate change, biodiversity loss, water loss, soil degradation, and hunger [1]. More recently, the issue of food waste has been linked to nutrition losses in diets [2,3], and these losses have important implications for the sustainability of diets and planetary health [4]. Efforts to prevent and reduce consumer food waste have included reducing cafeteria plate waste at an institutional level [5], changing guidelines around nutrition [6], food sharing apps [7], tailored home-based interventions [8], public commitments and goal setting [9], and information campaigns to increase food literacy.…”
Section: Introductionmentioning
confidence: 99%
“…The wasting of food produced for human consumption has been connected to issues such as climate change, biodiversity loss, water loss, soil degradation, and hunger [1]. More recently, the issue of food waste has been linked to nutrition losses in diets [2,3], and these losses have important implications for the sustainability of diets and planetary health [4]. Efforts to prevent and reduce consumer food waste have included reducing cafeteria plate waste at an institutional level [5], changing guidelines around nutrition [6], food sharing apps [7], tailored home-based interventions [8], public commitments and goal setting [9], and information campaigns to increase food literacy.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study led by Conrad and colleagues [3] found that higher quality diets were associated with greater amounts of food waste among American adults. Given the majority of food waste in households come from fruits and vegetables [4], it is possible that individuals who have a higher diet quality cook and prepare more of these foods, which could lead to more unavoidable (inedible portions, like stems or peels) waste through the preparation process. It is also possible that health conscious individuals purchase more healthful foods, such as fruits and vegetables, but fail to eat them before they spoil as a result of poor storage or planning, which could lead to more avoidable (edible portions) waste.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the economic and environmental impacts of food waste, waste of fruits and vegetables is also associated with the wasting of key nutrients of which many Canadians have inadequate intakes [18]. A recent analysis published by our team found that waste of avoidable fruits and vegetables was associated with substantial loss of bre, calcium, magnesium and vitamins A and C [4]. This suggests that many families in our sample have access to fruits and vegetables but are not consuming them.…”
Section: Discussionmentioning
confidence: 99%
“…Although some generalizations emerged from the study, there were notable cross-country differences -for instance, individuals residing in either the Czech Republic, Malta and Estonia were shown to have signi cantly lower amounts of food waste as compared to individuals residing in Denmark, Sweden, the Netherlands and Ireland [7]. Limited research has explored household food waste within the Canadian context using detailed waste audits [4,6,8] and no studies have examined the association between diet quality and food waste in Canada.…”
Section: Introductionmentioning
confidence: 92%